K2-161b: a low-density super-Neptune on an eccentric orbit. Issue 2 (29th November 2018) - Brahm, R; Espinoza, N; Rabus, M; Jordán, A; Díaz, M R; Rojas, F; Vučković, M; Zapata, A; Cortés, C; Drass, H; Jenkins, J S; Lachaume, R; et al.
ABSTRACT: We report the discovery of K2-161b, which was first identified as a planetary candidate from Kepler K2 photometry of Campaign 14, and whose planetary nature and orbital parameters were then confirmed with precision radial velocities. K2-161b is half as massive as Saturn (M_P= 0.179 ± 0.021 M_J ), and has a radius of R_P= 0.840 ± 0.011 R_J, which translates into a bulk density of ρ _P=0.37 ± 0.05 g cm^-3 . K2-161b transits its slightly evolved G-type host star (M_= 1.105 ± 0.019 M_, R_= 1.669 ± 0.022 R_ ) every 11.633 64 ± 0.000 10 d and presents a significantly eccentric orbit ( e = 0.420 ± 0.034). We estimate a relatively short circularization time-scale of 1.8 Gyr for the planet, but given the advanced age of the system we expect the planet to be engulfed by its evolving host star in ∼1 Gyr before the orbit circularizes. The low density of the planet coupled to the brightness of the host star ( J = 9.4) makes this system one of the best candidates known to date in the super-Neptune regime for atmospheric characterization via transmission spectroscopy, and to further study the transition region between ice and gas giant planets.